Long-term changes in jump performance and maximum strength in a cohort of NCAA division I women's volleyball athletes - Kavanaugh, A. A.; Mizuguchi, S.; Sands, W. A.; Ramsey, M. W.; Stone, M. H. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this investigation was to quantify the magnitude of change in maximal strength and jumping abilities over approximately 1, 2, and 3 years of supervised sport and resistance training in National Collegiate Athletic Association (NCAA) division I women's volleyball athletes. This was an exploratory study on a cohort of women's volleyball athletes (n = 29) split into 3 groups based on the length of the time spent in a supervised resistance training program: group 1 (n = 11): 0.7 ± 0.3 years, group 2 (n = 9): 1.6 ± 0.2 years, and group 3 (n = 9): 2.4 ± 0.6 years. Monitoring tests consisted of standing height (cm), body mass (kg), body fat (%), static jump height (SJH) and countermovement JH (CMJH) with 0-, 11-, and 20-kg loads (cm), and midthigh clean pull isometric peak force (IPF) and allometrically scaled IPF (IPFa) (N·kg-0.67). Increasing trends were observed for all variables from groups 1 to 2 to 3. Statistically greater improvements (p = 0.05) with moderate to large effect sizes were found between groups 1 and 3 for SJH 0 (19.7%, d = 1.35), SJH 11 (23.8%, d = 1.23), SJH 20 (30.6%, d = 1.20), CMJH 11 (22.6%, d = 1.18), IPF (44.4%, d = 1.22), and IPFa (41.2%, d = 1.32). A combination of traditional resistance training exercises and weightlifting variations at various loads, in addition to volleyball practice, seem to be effective at increasing maximal strength by 44% and vertical JH by 20-30% in NCAA division I women's volleyball athletes after about 2.5 years of training. Furthermore, these characteristics can be improved in the absence of additional plyometric training outside normal volleyball-specific practice.